Lapatinib plus Capecitabine for HER2-Positive Advanced-Stage Breast Cancer in Elderly Women: Review of the Anatolian Society of Medical Oncology (ASMO) Experience - DANE, FAYSAL (KARGER, 2013)
Background: The efficacy and safety of the lapatinib and capecitabine combination remain elusive in elderly patients with metastatic breast cancer (MBC), who progress after trastuzumab-based therapy. Patients and Methods: A total of 26 patients with HER2-positive MBC were included in this retrospective multicenter study. Median age was 69 years (range 65-82 years). All patients were treated with the combination of lapatinib (1,250 mg/day, continuously) and capecitabine (2,000 mg/m(2) on days 1-14 of a 21-day cycle). Data on demographics, clinical outcome, and toxicity were collected for descriptive analyses. Results: The median follow-up was 10 months (range 2-31 months). An overall response rate of 33.4% was achieved, including 1 complete response (3.8%), and 8 partial responses (30.8%). Median progression-free survival was 7 months (95% confidence interval (CI) 5-8), and the median overall survival was 15 months (95% CI 11-19). Most common side effects were fatigue (53.8%), diarrhea (46%), vomiting (36.3%), hand-foot syndrome (34.5%), and anorexia (34.6%). Grade 3-4 toxicities were identified as hand-foot syndrome (3.8%), diarrhea (7.6%), and fatigue (11.5%). There were no symptomatic cardiac events. Conclusion: Lapatinib and capecitabine combination therapy was effective and well tolerated in elderly patients with MBC, who had progressive disease after trastuzunnab-based therapy.
Keywords: Advanced breast cancer; Elderly women; Lapatinib; Capecitabine; HER2; OLDER; AGE